A Special Military Operation in the Context of Russia's Interpretation - Jaroslav Galga; Ján Spišák (Vojenské rozhledy, 2023)
The Russia has presented the ongoing war in Ukraine by the term special military operation, whose goals were declared by Russian President Putin in terms of demilitarization and denazification of Ukraine. In the wider context, there is an imperial effort of Russia to enforce its power and influence in the region by an offensive and aggressive war. The authors define the fundamental difference between a special operation and the so-called special military operation in the context of contemporary interpretation of the Kremlin. They further argue the way in which Russia is trying to justify the war and discuss its reality in terms of international law.